Uwarunkowania środowiskowe zmian strukturalnych w Polsce i Unii Europejskiej - Borys, Tadeusz; Ładysz, Jerzy (Environmental Issues of Structural Changes in Poland and the European Union, 2007)
Nowadays there is more and more strengthening of the dependence between size of pollution and condition of environment and also between size, structure of production and size of natural resources. Size of pollution, its chemical and spatial structure depends first of all on brand, spatial and product structure of economic activity and on structure of natural resources using. Environmental policy in Poland and the European Union has significant restrictive influence on the forming of economic structures. Growing implementation of environmental restrictions in the structural policy, beside all better and common application of environmental technologies, will contribute to modernization of national economies of member states of the European Union, to increasing their technological creativeness and to the development of new markets causing creation of new jobs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 217-230